ANTROPOGENIC ENVIRONMENTAL CHANGES AFTER ACCUMULATION OF SOLID HOUSEHOLD WASTE (Regional aspects of productive forces development of Ukraine, 2024)
Introduction. Ensuring effective waste management to reduce its volume and negative impact on the environment is an extremely important issue today. To improve the situation, strategies should be implemented to reduce the amount of waste and recycle it. An important step is the introduction of recycling and reuse systems, as well as active public education to foster a responsible attitude towards waste. In particular, the development of technologies aimed at reducing waste generation at the stage of its production plays a key role in this process.Objective. To analyze the literature and assess anthropogenic environmental changes under the influence of municipal solid waste (MSW) accumulation.Research methods. In order to summarize the available knowledge, identify trends in the study of these thematic areas and identify possible gaps for further research, a literature review was used:Ukrainian and foreign authors with a focus on the keywords “household waste”, “anthropogenic changes” and “environment”.Results. Population growth leads to an increase in the volume of waste - substances, materials and objects generated in the course of human activity that cannot be further used at the place of theirgeneration or discovery. The problem of recycling and utilization of household waste is becoming one of the first in the world. This is especially true in large cities with high population density, where millions ofcubic meters of various types of waste are accumulated annually.Conclusions. One of the main environmental and hygienic tasks is the construction of waste recycling complexes and further reduction of the unrecycled part of solid waste, as well as the introduction of waste-free technologies at the city's enterprises.